A file of processed gravity data for the Rukwa-Tanganyika Rift Zone, including the sediment- and mantle-corrected gravity data and the Moho depth estimates derived from power spectral analysis - Emmanuel A Njinju; Estella A Atekwana (PANGAEA, 2025)
The Rukwa-Tanganyika Rift Zone (RTRZ), experiencing multiphase rifting, forms the nonvolcanic southern part of the Western Branch of the East African Rift. We investigate the crustal structure beneath the RTRZ to understand how strain migrates beneath multiphase rifts. We use Bouguer gravity data from the World Gravity Map 2012 (Balmino et al., 2012; Bonvalot et al., 2012) and power spectral analysis to estimate the depth to Moho beneath the RTRZ. We correct for the effect of sediments and the deep mantle from the Bouguer gravity data. The deep mantle gravity is obtained by scaling the S40RTS global seismic tomography model (Ritsema et al., 2011) into equivalent deep mantle density anomalies using a velocity-to-density scaling factor of 0.15 (e.g., Behn et al., 2004; Conrad et al., 2007; Conrad & Behn, 2010). The gravity anomaly g(r) of the deep mantle is forward calculated from the deep mantle density anomalies using the Gauss-Legendre Quadrature (GLQ) elemental integration. Similarly, the gravitational effect of the known sedimentary basins (from CRUST1.0; Laske et al., 2013) is forward calculated numerically using the GLQ elemental integration (Asgharzadeh et al., 2007; Uieda et al., 2016; Uieda & Barbosa, 2017). Here we include a data file of the processed gravity data for the RTRZ, including the sediment- and mantle-corrected gravity data and the Moho depth estimates derived from power spectral analysis of the gravity data. The dataset consists of eight columns representing the different parameters measured with units in []: (1) Longitude (2) Latitude (3) Bouguer_GRAVITY_WGM2012 [mGal] (4) Sediment_Thickness [m] (5) Moho Depths [km] (6) Mantle_Gravity [mGal] (7) Sediment_Gravity_Effect [mGal] (8) Gravity_Effect_of_Deep_Mantle_and_Sediments [mGal].